141k views
1 vote
Im having a really hard time rn ;-;
2(a + 6) – 3(a – 5) = 18

1 Answer

4 votes

Answer: A= 9

Explanation:

2(a+6)-3(a-5)=18

FIRST YOU WANT TO DISTRUBUTE THE PARENTHESIS

2a + 12 -3a + 15 =18

ADD AND SUBTRACT LIKE TERMS

-1a + 27 = 18

SUBTRACT 27 ON BOTH SIDES

-1a + 27 =18

- 27 -27

-1a= -9

DIVIDES -1 ON BOTH SIDES AND NEGATIVES CANCEL OUT SO IT WOULD BE

A= 9

User Riccardo Bucco
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.